2021
DOI: 10.3390/ijerph18168833
|View full text |Cite
|
Sign up to set email alerts
|

Could Kallikrein-Related Serine Peptidase 3 Be an Early Biomarker of Environmental Exposure in Young Women?

Abstract: Bisphenols and phthalates affect androgen receptor-mediated signaling that directly regulates Kallikrein-Related serine Peptidase 3 (KLK3) secretion, indicating that environmental factors may play a role in KLK3 secretion. With the aim of obtaining preliminary data on whether KLK3 could serve as an early marker of environmental pollution effects, in 61 and 58 healthy women living in a high environmental impact (HEI) and low environmental impact (LEI) area, respectively, serum KLK3 levels at different phases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Environmental pollution also has a significant bearing on the susceptibility of a given population to various diseases, and semen quality has been found to be a potential indicator of susceptibility to viral insults in those highly polluted areas, capable of helping to predict the risk of harmful effects of viral outbreaks [ 227 , 228 ]. Very recently it has also been demonstrated that kallikrein-related serine peptidase 3 appears to be an early biomarker of environmental exposure in young women [ 229 ]. For these reasons, biosensors have been developed for environmental pollution along with new technologies, especially because altered environmental conditions, together with the direct and indirect short- and long-term effects of viral infection, have the potential to produce a deterioration in sperm quality with significant implications for male fertility, particularly in those areas with a greater environmental impact [ 230 ].…”
Section: Effects Of Pcbs On Human Healthmentioning
confidence: 99%
“…Environmental pollution also has a significant bearing on the susceptibility of a given population to various diseases, and semen quality has been found to be a potential indicator of susceptibility to viral insults in those highly polluted areas, capable of helping to predict the risk of harmful effects of viral outbreaks [ 227 , 228 ]. Very recently it has also been demonstrated that kallikrein-related serine peptidase 3 appears to be an early biomarker of environmental exposure in young women [ 229 ]. For these reasons, biosensors have been developed for environmental pollution along with new technologies, especially because altered environmental conditions, together with the direct and indirect short- and long-term effects of viral infection, have the potential to produce a deterioration in sperm quality with significant implications for male fertility, particularly in those areas with a greater environmental impact [ 230 ].…”
Section: Effects Of Pcbs On Human Healthmentioning
confidence: 99%
“…Communities living in polluted areas are recognized to experience a higher incidence of cancer, NCDs and male infertility. Therefore, in parallel to regulatory actions, evidencebased lifestyle intervention models should be designed in order to mitigate the impact of environmental pollutants on human health [63,[87][88][89][90][91].…”
Section: Mediterranean Dietmentioning
confidence: 99%
“…Evidence are provided that, along with a threat to female fertility, the BPA's main deleterious effects are associated with offspring development during perinatal exposure, possibly generating dysregulation of the hypothalamic-pituitaryovarian axis, placing the following generations at risk of developing BPA-related diseases themselves [61]. Furthermore, BPA has been proven to affect female androgen receptormediated signaling, which regulates Kallikrein-Related serine Peptidase 3 secretion [62].…”
Section: Environmental Chemical Stressorsmentioning
confidence: 99%